PERAN PONDOK PESANTREN DAARUL FIKRI DALAM MENINGKATKAN NILAI RELIGIUS MASYARAKAT KAMPUNG BEKASI - Farid Robby Rodiya; Gunawan Ikhtiono; Sutisna Sutisna (Universitas Pahlawan Tuanku Tambusai, 2022)
Islamic boarding schools as educational institutions and Islamic institutions that act as distributors of agents of change, namely the students make a major contribution to the community in the pesantren environment and the wider community. Pesantren opens opportunities for the community to participate and play a role in the activities in the pesantren. The effectiveness of the empowerment role carried out by pesantren will be maximized if the pesantren is able to equip itself with skilled and professional personnel to manage various activities that involve the community. It is also necessary for caregivers related to the role of pesantren, in addition to having social sensitivity, they must also have broad insight on how to build a religious society. Religion itself can be defined as a person's appreciation of religious values ​​that are believed to be in the form of obedience and applied in daily behavior. Seeing the background of the problem, a question arises, how is the role of the Daarul Fikri Islamic boarding school in increasing the religious values ​​of the people of the Bekasi Warung Bambu Village. The aim of this research is to find out the role of pesantren and what activities are carried out in increasing the religious values ​​of the community in the pesantren environment. The type of research that the researcher uses is field research which is descriptive qualitative, the data sources used are primary and secondary data sources, while the data collection techniques use interviews, observation and documentation. Interviews were conducted with the administrators of the pesantren and the surrounding community, observations were made by observing the conditions in the pesantren and around the pesantren. Documentation is used to support the data that researchers get in the field. Based on the results of research that has been carried out, the Daarul Fikri Islamic Boarding School has held activities that lead to increasing the religious values ​​of the community, including traveling Subuk (Flute), Elderly Islamic Boarding School, Clean Friday, Santri serving. In addition to the activities held by community boarding schools, they often involve pesantren in some of the religious activities they carry out, this is an opportunity for the cottage to continue to broadcast Islam in the community. Keywords: Islamic Boarding School, Community, Religious Values